Identification of differentially expressed proteins as biomarkers of acute myeloid leukaemia - Barantalab, Fatemeh (2014)
Acute myeloid leukaemia (AML) is a hematopoietic malignancy characterized by aberrant proliferation of myeloid progenitor cells, coupled by a partial block in cellular differentiation. Sixty-five to 75% of younger AML patients will achieve complete remission (CR) after induction therapy, while the rate of CR is lower in elderly patients (40-50%). Most patients who achieve CR will relapse within three years and those who do not respond to induction therapy display resistance to chemotherapy. Therefore, resistance to chemotherapy is a major problem in treatment of patients with AML. Current prognostic markers include age, total white blood counts and certain chromosomal translocations. However in half of the patients, these markers are not adequate. Unlike genomics, screening for potential prognostic markers using proteomics is less frequently conducted due to its more laborious and time-consuming nature. This includes for acute myeloid leukaemias. The aims of this thesis were to establish a twodimensional gel electrophoresis (2-DE) method for protein extracts from peripheral blood mononuclear cells (PBMC) and plasma samples from acute myeloid leukaemia patients. This proteomics approach will be exploited to identify potential biomarkers that may be associated with resistance to chemotherapy at initial diagnosis before treatment. Ten samples were chosen for 2-DE analysis of PBMC (7 Resistant and 3 Responsive) and plasma (6 Resistant and 4 Responsive). LC-MS/MS and MALDI-TOF/TOF were used for identification of selected PBMC and plasma proteins, respectively. Real time RT-PCR was applied to confirm proteomics results of differentially expressed proteins in PBMC. For validation of 2-DE results of plasma firstly, a monoclonal antibody was produced against selected proteins from 2-DE analysis. Western blot was used to screen hybridoma and to validate proteomic results of plasma. HnRNP H1, ACADS and Putative Uncharacterised Protein in Bacteria were identified as differentially expressed proteins in PBMC. ACADS and Putative Protein were upregulated in the resistant group while and HnRNP H1 showed higher expression in the responsive group. By performing blast search of matched peptide of Putative Protein to NCBI database against homo sapiens, DNA-PK was found as a hit. This protein along with two additional HnRNPs-related proteins (HnRNP K, HnRNP A1) was used for further analysis by real time RT-PCR. Quantitative RT-PCR with 16 AML samples (8 resistant and 8 responsive) confirmed the 2-D analysis on PBMC (using HnRNPH1, ACADS and DNA-PK and two additional HnRNPs related genes, HnRNP K and A1) at the gene expression level. HnRNP K was found to be a highly expressed in responsive group. No difference was observed in mRNA expression level of HnRNP A1 between resistant and responsive groups. ACADS and DNA-PK represented significantly higher expressions in resistant group (p<0.05). In 2-DE analysis of plasma, eight proteins were differentially expressed significantly between plasma of resistant and responsive patients. Selected spots were divided into three groups on the basis of their position on 2D gel, Molecular Weight (HMW, MW=70kDa) spots were obviously detectable in three samples of resistant group but it was not seen in responsive and normal samples, while identified protein APO E (MW=36 kDa) and low molecular weight spots No. 177 and 173 (MW < 20kDa) were overexpressed in the responsive group (p <0.03) using Mann Whitney U test. Protein spots HMW and No. 177 and 173 were excised from gel and used as antigen for antibody production. By western blot screening of hybridoma, clone 3-16 was selected for screening on AML samples. Signals of HMW spots were obtained by 2-DE western blotting of this hybridoma using anti-mouse IgG as a secondary antibody. The results of 2-DE western blot on 16 AML samples confirmed the results of 2-DE analysis of plasma. No antibody was found for spots No. 177 and 173. In conclusion, gel-based proteomic approach is a good technique for selection of differentially expressed proteins and identification of potential biomarkers in AML patients with differential response to chemotherapy. HnRNP K but not HnRNP A1 may be useful to identify AML patients responsive to chemotherapy. ACADS and DNA-PK may have potential for identification of resistant patients. Furthermore, the monoclonal antibody generated in this study may be useful in differentiating resistant patient. In general, the proteins identified in this study and the generated antibody may have potential to predict response to induction chemotherapy in AML patients at diagnosis.